Perancangan Sekolah Terpadu Internasional Di Kota Bekasi Dengan Pendekatan Arsitektur Ramah Lingkungan - Bayu Puji Hartoyo; Tri Endangsih; Putri Suryandari (MAESTRO, 2023)
The International School is a sample of national schools in Indonesia with international quality standards. With Permendiknas regulation no. 78 of 2009 concerning the Organization of International Standard Schools. Having a teaching and learning process at this school emphasizes the development of creativity, innovation, and experimentation to spur new ideas that have never existed. International standards demanded in SBI are graduate competency standards, curriculum, teaching and learning processes, human resources, facilities, management, financing and assessment of international standards. So that this international school also aims for students who want to more easily continue studying abroad because they already use an international curriculum. With the theme of international standard school design, this is a school for the future, with an environmentally friendly architectural design approach. Ecological technology as the main element of design consideration, which is expected to support each other and in accordance with the planned building functions. In creating a work with environmentally friendly architecture what is needed is an understanding that everything on earth has an influence on the environment.